Culture Shock: Challenges of International Students - Mulyadi, Eko; Permatasari , Dian; Soares , Domingos; Syarifudin, Muhamad; da Silva Pinto , Terezinha; Sarmento, Julio (CV. AFDIFAL MAJU BERKAH, 2024)
In the globalized landscape of higher education, the number of students seeking academic opportunities abroad has surged. This literature review investigates the cultural shock experienced by international students, examining its scale and impact globally and within Asia. The method used the PRISMA checklist and flowchart for selection and review of journals, consisting of three stages: identification from databases (n = 3,874,770), screening (n = 157), and inclusion (n = 10). Additionally, information was sought from books, dissertations, unpublished materials, and personal experiences as a teacher of international students. The review identified three themes regarding cultural shock. The first theme, Cultural Shock Syndromes, reveals that students generally experience homesickness, a desire to escape their new environment, and distress. The second theme, Aspects of Culture Shock Experienced by Students, includes language barriers, daily schedules, non-verbal communication, homesickness, loneliness, seasons and weather, and food. The third theme, Effects of Culture Shock on Students’ Lives during their Study, focuses on academic performance, social integration, and overall well-being. The conclusion is that cultural shock significantly affects international students as they navigate new academic and social environments, encompassing challenges such as homesickness, social exclusion, identity confusion, and cultural dissonance. These factors collectively contribute to heightened stress and anxiety, negatively impacting students' academic performance and overall well-being. Understanding the specific complaints and challenges associated with cultural shock highlights the critical need for comprehensive support systems.